FACTORS RELATED TO MATERNAL MORTALITY IN THE REGION LORETO, 1999-2002 - Vásquez Vásquez, Javier (2015)
OBJETIVE: To determine the relationship between some factors, including delays described by Thadeus and Maine, and maternal mortality. DESIGN: non-experimental, transversal, correlational and retrospective study. MATERIALS AND METHODS: Data collection was performed using the technique of analysis of secondary data sources (epidemiological research records of maternal death). To find the relationship between maternal mortality and factors parametric chi-square test was used. RESULTS: During the study period (1999-200) reports of 124 maternal deaths were found. The reason was 194.7 maternal deaths per 100,000 live births. The direct causes accounted for 54.1% of all maternal deaths and within the bleeding was 33.9%, hypertensive disease of pregnancy 8.9% and 8.1% infections. Indirect causes meant 43.5% and within severe malaria accounted for 14.5%. No statistically significant relationship between maternal death and maternal age, parity, place of origin, place of death, civi status, level of education, at the beginning of prenatal care and interval between the last prenatal and found time of death. statistically significant relationship between maternal death and gestational age (p = 0.01223), postpartum (p = 0.000001), absence or deficiency of prenatal care (p = 0.0255) was found, the delay in applying help (p = 0.01869) and the delay in the transfer of the patient (p = 0.01869). The latter two by Thadeus and Maine.